RNA binding protein RALY activates the cholesterol synthesis pathway through an MTA1 splicing switch in hepatocellular carcinoma. (10th July 2022) - Qiao, Yejun; Shi, Qili; Yuan, Xu; Ding, Jie; Li, Xinrong; Shen, Mengting; Huang, Shenglin; Chen, Zhiao; Wang, Lu; Zhao, Yingjun; He, Xianghuo
Abstract: Alternative splicing is an important RNA processing event that contributes to RNA complexity and protein diversity in cancer. Accumulating evidence demonstrates the essential roles of some alternatively spliced genes in carcinogenesis. However, the potential roles of alternatively spliced genes in hepatocellular carcinoma (HCC) are still largely unknown. Here we showed that the HnRNP Associated with Lethal Yellow Protein Homolog (RALY) gene is upregulated and associated with poor outcomes in HCC patients. RALY acts as a tumor-promoting factor by cooperating with splicing factor 3b subunit 3 (SF3B3) and modulating the splicing switch of Metastasis Associated 1 (MTA1) from MTA-S to MTA1-L. Normally, MTA1-S inhibits cell proliferation by reducing the transcription of cholesterol synthesis genes. In HCC, RALY and SF3B3 cooperate to regulate the MTA1 splicing switch, leading to a reduction in the MTA1-S level, and alleviating the inhibitory effect of MTA1-S on cholesterol synthesis genes, thus promoting HCC cell proliferation. In conclusion, our results revealed that the RALY-SF3B3/MTA1/cholesterol synthesis pathway contributes essentially to hepatic carcinogenesis and could serve as a promising therapeutic target for HCC. Highlights: RALY is frequently increased in HCC and promotes HCC cells proliferation in vitro and in vivo. RALY-SF3B3 complex activates the cholesterol synthesis pathway and promotes cholesterol production in HCC cells. In HCC cells, RALY-SF3B3 complex affects the alternative splicing of MTA1, inducing switch from MTA1-S to MTA1-L, with MTA1-exon 4 involved. Down-regulated MTA1-S relieves the transcription suppression of cholesterol synthesis-related genes, thus promoting the proliferation rate and colony formation ability of HCC cells.